A suggested classification guide for PACS client applications: the five degrees of thickness...picture archiving and communication systems - Toland C; Meenan C; Toland M; Safdar N; Vandermeer P; Nagy P (Journal of Digital Imaging)
This article defines and describes the numerous types of 'clients' for picture archiving and communication systems (PACS). A radiologist uses a client to view images stored in the system. Many PACS are available in the market, and each offers different methods by which a client can view images from the server. The terminology used to describe these different methods can cause confusion and lead to poor choice for those imaging team members who are given the task of purchasing, implementing, and supporting the PACS. We propose a classification of clients with respect to their impact on client work stations, an effect often referred to as the application's thickness. The thinner the client, the less effect it has on the hosting work station. In contrast, a thick client consumes the work station's resources and often prevents a work station from being used to effectively run anything other than the client application. Functionality and supportability are highlighted as key and interacting metrics in determining optimal correct PACS solutions. The importance of a clear understanding of the needs and requirements of all users as well as the client application is emphasized. This relationship between supportability and functionality becomes increasingly important as the industry shifts to enterprise information technology solutions.